2020
DOI: 10.3390/genes11020228
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals Stem Secondary Growth of Grafted Rosa rugosa ‘Rosea’ Scion and R. multiflora ‘Innermis’ Rootstock

Abstract: Grafted plant is a chimeric organism formed by the connection of scion and rootstock through stems, so stem growth and development become one of the important factors to affect grafted plant state. However, information regarding the molecular responses of stems secondary growth after grafting is limited. A grafted Rosa plant, with R. rugosa ‘Rosea’ as the scion (Rr_scion) grafted onto R. multiflora ‘Innermis’ as the stock (Rm_stock), has been shown to significantly improve stem thickness. To elucidate the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…6). Previous studies have reported that physiological differences are strongly correlated with gene expression changes in the scion after grafting and some genes of the scion are upregulated or downregulated by rootstocks (Sun et al 2020). In this study, the activities of IAI, SPS, and SuSy decreased in grafted watermelon lines vs. own-root watermelon lines.…”
Section: Discussionmentioning
confidence: 45%
“…6). Previous studies have reported that physiological differences are strongly correlated with gene expression changes in the scion after grafting and some genes of the scion are upregulated or downregulated by rootstocks (Sun et al 2020). In this study, the activities of IAI, SPS, and SuSy decreased in grafted watermelon lines vs. own-root watermelon lines.…”
Section: Discussionmentioning
confidence: 45%
“…Combined with biomass allocation, one reason might be that plants would allocate relatively more biomass to their underground parts under water deficit conditions, thereby increasing the absorption and utilization of limited resources (Shipley and Meziane, 2002). Another reason might be that the scion also conferred vigor to the rootstock (Sun et al, 2020) and female rootstocks altered the secondary growth (stem thickness) (P < 0.05) rather than the primary growth (stem length) (P > 0.05) (Cookson and Ollat, 2013). It is evident the growth differences between females and males under well-watered conditions are predominantly linked to shoots, as higher plant height and biomass were observed in female seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in cultivation and for the improvement of crops, due to its low cost, simple operation, high value of use, and other advantages [ 17 ]; for some difficult-to-graft plants, such as walnuts, factors such as temperature, humidity, and treatment methods of grafting materials must be taken into account when grafting [ 18 ]. Previous studies have found that the grafting technique is an effective way to study plant molecular communication signals and the exchange of genetic material [ 19 ]. The accumulation of biomass in the scion part and the response to abiotic stress can be changed depending on different rootstocks [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%